Inversión, Gastos Directos y Margen Bruto de Almácigos Flotantes de Tabaco - Piccolo, Maria Alejandra; Galli, Juan Alberto; Baldi, Javier Anibal (EEA Salta, INTA, 2022)
Estación Experimental Agropecuaria Salta